2021
DOI: 10.1186/s12870-021-03298-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nanophos in agriculture to improve functional bacterial community and crop productivity

Abstract: Background Since the World’s population is increasing, it’s critical to boost agricultural productivity to meet the rising demand for food and reduce poverty. Fertilizers are widely used in traditional agricultural methods to improve crop yield, but they have a number of negative environmental consequences such as nutrient losses, decrease fertility and polluted water and air. Researchers have been focusing on alternative crop fertilizers mechanisms to address these issues in recent years and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 69 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…Tarafdar et al (2013) reported significant improvement of rhizospheric microbial population and activities of acid and alkaline phosphatase and phytase in cluster bean rhizosphere when treated with ZnONPs (10 mg L −1 ). Application of nanophos, which consists of the phosphate solubilizing bacteria, also improved the different soil enzyme activities under maize cultivation (Chaudhary et al, 2021e). Silver NPs were not affected by the soil enzyme activities but decrease the β-glucosidase activity was maximum in T8 and T9 treatments in the experimental soil throughout the experimental period.…”
Section: Soil Enzyme Activitymentioning
confidence: 89%
“…Tarafdar et al (2013) reported significant improvement of rhizospheric microbial population and activities of acid and alkaline phosphatase and phytase in cluster bean rhizosphere when treated with ZnONPs (10 mg L −1 ). Application of nanophos, which consists of the phosphate solubilizing bacteria, also improved the different soil enzyme activities under maize cultivation (Chaudhary et al, 2021e). Silver NPs were not affected by the soil enzyme activities but decrease the β-glucosidase activity was maximum in T8 and T9 treatments in the experimental soil throughout the experimental period.…”
Section: Soil Enzyme Activitymentioning
confidence: 89%
“…Microbial biofertilizers are increasingly applied in agricultural activities to improve plant growth, yield, and quality via phytohormone production, phosphate solubilization, promoting secondary metabolite accumulation, and adjusting imbalanced soil microbial communities in harsh soil environments. , It was reported that the application of Trichoderma sp. in combination with G.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial biofertilizers are increasingly applied in agricultural activities to improve plant growth, yield, and quality via phytohormone production, 38 phosphate solubilization, 39 promoting secondary metabolite accumulation, 40 and adjusting imbalanced soil microbial communities in harsh soil environments. 39,41 It was reported that the application of Trichoderma sp. in combination with G. versiforme could improve the content of Sal B and Tan IIA in SM roots under CC conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, microbes with plant growthpromoting (PGP) traits have been isolated and used as inoculants to improve crop production (Finkel et al, 2017;Banerjee et al, 2018;de Souza et al, 2020). Microbes assist plant growth either by enhancing nutrient acquisition such as nitrogen fixation, phosphorus solubilization, and siderophore production or producing plant growth promoting substances (Olanrewaju et al, 2017;Saleem et al, 2018;Chaudhary et al, 2021;Joshi et al, 2021). In addition, microbial inoculants have the potential to suppress several pathogenic organisms (Yasmin et al, 2016;Olanrewaju et al, 2017;Abbasi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%